Pengaruh Green Marketing dan Brand Awareness terhadap Purchase Decision pada The Body Shop - Rohmah, Dali Sofiatu; Tobing, Rudy P. (CV. Lenggogeni Data Publishing, 2023)
This study aims to determine the effect of green marketing and brand awareness on purchase decisions at The Body Shop, one of the beauty companies in Indonesia that has implemented the concept of green marketing in its marketing process. This research was conducted using a quantitative approach with a total sample of 195 respondents. The instrument used in this research is a questionnaire. Instrument testing includes validity and reliability tests. Data analysis used descriptive analysis, while testing the hypothesis used multiple linear regression analysis along with the t test, f test, and R2 test. The results of the study show that (1) green marketing influences purchase decisions; (2) brand awareness influences purchase decisions; and (3) green marketing and brand awareness simultaneously influence purchase decisions. This research was only conducted on The Body Shop consumers who had made purchases through the Tokopedia marketplace. Keywords: green marketing, brand awareness, purchase decision, beauty product, the body shop